Comparison of Reverse Transcription Quantitative Real-Time PCR, Flow Cytometry, and Immunohistochemistry for Detection of Monoclonality in Lymphomas. (4th February 2014) - Ståhlberg, Anders; Åman, Pierre; Strömbom, Linda; Zoric, Neven; Diez, Alfredo; Nilsson, Olle; Kubista, Mikael; Ridell, Börje
Abstract : In healthy humans, 60–70% of the B lymphocytes produce kappa light chains, while the remaining cells produce lambda light chains. Malignant transformation and clonal expansion of B lymphocytes lead to an altered kappa : lambda expression ratio, which is an important diagnostic criteria of lymphomas. Here, we compared three methods for clonality determination of suspected B cell lymphomas. Tumor biopsies from 55 patients with B cell malignancies, 5 B-lymphoid tumor cell lines, and 20 biopsies from patients with lymphadenitis were analyzed by immunohistochemistry, flow cytometry, and reverse transcription quantitative real-time PCR. Clonality was determined by immunohistochemistry in 52/53 cases, flow cytometry in 30/39 cases, and reverse transcription quantitative real-time PCR in 33/55 cases. In conclusion, immunohistochemistry was superior to flow cytometry and reverse transcription quantitative real-time PCR for clonality identification. Flow cytometry and reverse transcription quantitative real-time PCR analysis has complementary values. In a considerable number of cases tumor cells produced both kappa and lambda light chain transcripts, but only one type of light chain peptide was produced.